The Effect of Excess Heat Utilization on the Production Cost of Cement - Olayide R. Adetunji; Montfort C. Ogbuokiri; Olawale U. Dairo; Olanrewaju B. Olatunde; Iliyas K. Okediran (Mechanical Engineering for Society and Industry, 2021)
Industrial excess heat is a largely untapped resource that has the potential for external use that would be beneficial to the cement industry. Therefore, this work studied the excess heat utilization for the optimization of production cost in a cement plant within a period of three years. The study of plant layout in the selected plant in Nigeria (Ewekoro II Cement Plant of 200 tonnes/hour) was carried out to identify areas where excess heat is generated. The temperature and static pressure of precalciner, kiln, and cyclone were taken using a temperature probe, pitot tube, digital manometer, and light-emitting diode temperature reader. These parameters were used to obtain the mass flow rate and heat transfer needed for the heat energy analysis of the system. The kiln was maintained at constant tonnage per hour through a clinker truck weighed using the weighbridge. The result showed that the heat generated from the kiln was 577,640,260 MJ/hr. through excess air draft of 780,000 m3/hr (89.4%) at 250 °C and induced draft fan of 900,000 m3/hr at 350 °C. The result showed that excess heat can be utilized in pre-heater and air quenched cooler boilers, steam turbines and auxiliaries, and generators. The total estimated heat that could be saved amounted to 344,648,250 MJ with a total annual capacity of 2.25 million tonnes of cement. A saving of over two billion dollars could be achieved in production cost per year.